Numerical investigation of solar radiation effect on passive and active heating and cooling system of a concept museum building. (1st October 2020) - Vaseghi, M.; Fazel, M.; Ekhlassi, A.
Highlights: Passive and active ventilation system for a special concept museum building. Suggested active method is able to compensate passive leakage energy. Proposed active ventilation method is able to provide lots of energy required. Active ventilation method is imperative only in two hours during the winter days. Passive ventilation method is able to reduce temperature up to 4 degrees in summer days. Abstract: In this research, a passive and active ventilation system for a particular concept museum building has been proposed and evaluated using CFD simulation. The passive method is heating by solar radiation, and the active approach is hot water circulating in spiral pipes. The result shows that desired thermal comfort can be achieved for the occupant zone in the coldest day of winter. The HVAC CFD simulation has been carried out between 10 AM and 5 PM, indicate that at both 10 AM and 5 PM, the average temperature of the occupant zone is less than the comfort level, and it is imperative to apply the floor heating system as an active method. Three different velocities, 0.3, 0.2 and 0.1 m/s are used for hot water and evaluated. Finally, thermal comfort can be reached by pumping hot water at velocity of 0.1 m/s and 0.3 m/s, respectively. Also, in summer, due to overheating phenomena in some hours, a method considering the stack effect is designed and evaluated that it is led to reducing the average temperature up to 5 degrees. Also, the air volume flow rate is 20.49  m 3 / s, and air changes per hour is 13.85, that is entirely appropriate for the museum building.